Pengaruh Self Efficacy Terhadap Hasil Belajar Matematika Siswa Kelas III SD Kristen Kondo Sapata, Makassar, Indonesia - Hesnimati Rahman (PINISI :Journal of Teacher Professional, 2020)
This reseacrh to knowing of students of class III SD Kristen Kondo Sapata. This research was an “ex-post facto” research which was co relational. The population in this study was all class III at SD Kristen Kondo Sapata which also became a research sample. The result of descriptive statistical analysis showed that the average score of mathematics learning outcomes of students in 2018/2019 academic year was 67,88285 and was in the high category with a standard deviation of 19,33323. The average score of self-efficacy was 74,73 and included in the high category with a standard deviation of 13,492. The result of inferential statistics analysis showed that self-efficacy had a positive effect on the learning outcomes of class III SD Kristen Kondo Sapata students with a contribution of 61.8%.